(untitled) (Texas Journal of Philology, Culture and History, 2025)
The article discusses the life of Zahiriddin Muhammad Bobur. Тhe significance of the work “Boburnoma” in the study of historical toponymy itsinterpretations, explanations and notes on the historical toponyms of the present-day Namangan region of the Republic of Uzbekistan and its analysis are given. Based on the materials of the work, the historical variants and linguistic development of current toponyms belonging to the toponymy of the Namangan region are highlighted